GEJALA MORFOFONEMIK PADA TUTURAN ANAK-ANAK SUNDA DI WILAYAH PANGANDARAN - Dewi, Nida Kania; Astuti, Dewi Siti (Prodi Pendidikan Bahasa dan Sastra Daerah, 2018)
The study on morphophonemic symptoms of sundanese especially on children in Pangandaran RT 03 RW 08 Dusun Parapat Kec. Pangandaran was conducted due to many uniqueness in the language that spoken. It examines the symptoms of morphophonemic and the level found in morphophonemic symptoms of children who speak Sundanese. The method used in this research was qualitative. While recording the oral data source gained in area was used to collect the data. The techniques of analysis is focused on the symptoms of morphophonemic especially on basic morpheme and any level that experience symptoms of morphophonemic. The results obtained from this research are monomorphic and polymorphic monomorphic and polymorphic. Phrases include verb phrases, noun phrases, adjective phrases and adverb phrases. While meanings include lexical meanings and grammatical meanings.